الاستقبال الحسي الداخلي والذاكرة الجسدية للإنفعال لدى المراهقين المصابين باضطراب طيف التوحد (Comprehensive Journal of Science, 2026)
This study aimed to explore the nature of the relationship between Interoception and Emotional Somatic Memory in a sample of adolescents with Autism Spectrum Disorder (ASD). Deficits in interoception pose a fundamental challenge, hindering these adolescents’ ability to perceive and interpret internal physiological signals, which negatively impacts emotional regulation. The study seeks to identify the distinct patterns of storing and recalling emotion-related bodily responses (somatic memory) in light of this sensory deficit. The study concludes that understanding this relationship provides a new theoretical framework for developing intervention programs aimed at improving internal sensory awareness as an entry point to enhance emotional and behavioral competence in adolescents with ASD
Keywords: Interoception, Somatic Memory, Emotion, Adolescents, Autism Spectrum Disorder.